2015
DOI: 10.1086/680523
|View full text |Cite
|
Sign up to set email alerts
|

Relative impacts of morphological alteration to shorelines and eutrophication on littoral macroinvertebrates in Mediterranean lakes

Abstract: Development of effective methods for assessing the ecological status of lakes based on littoral benthic fauna has been hampered by the lack of quantitative data on the relative impacts of key pressures on the benthic community. We used variance partitioning at 126 sites belonging to 14 natural Mediterranean lakes to analyze the pure and shared effects of eutrophication, morphological alterations, microhabitat type, lake morphometry and geographic position on the littoral macroinvertebrate community. The spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 66 publications
1
21
2
Order By: Relevance
“…Our results seemingly support the conclusion of Urbanič (2014b), indicating the possible dominance of eutrophication when assessing hydromorphological alterations of different lake types. In contrast to our findings, many researchers reported that local (morphological/habitat) variables dominate over within-lake variables (eutrophication) in shaping littoral benthic assemblages (Tolonen et al, 2001;McGoff and Sandin, 2012;Pilotto et al, 2015). The reason for discrepancy might be that in the mentioned studies temporal and spatial variability were not taken into consideration.…”
Section: Teasing Apart Drivers Of Littoral Benthic Assemblagescontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results seemingly support the conclusion of Urbanič (2014b), indicating the possible dominance of eutrophication when assessing hydromorphological alterations of different lake types. In contrast to our findings, many researchers reported that local (morphological/habitat) variables dominate over within-lake variables (eutrophication) in shaping littoral benthic assemblages (Tolonen et al, 2001;McGoff and Sandin, 2012;Pilotto et al, 2015). The reason for discrepancy might be that in the mentioned studies temporal and spatial variability were not taken into consideration.…”
Section: Teasing Apart Drivers Of Littoral Benthic Assemblagescontrasting
confidence: 99%
“…Hence, our results imply that benthic invertebrates could be good indicators for gradients along natural characteristics of lakes, intensive agriculture, omnivorous fish, urbanization and nutrient concentrations. The tolerance structure of benthic invertebrate taxa along substratum gradient exhibited a surprisingly bigger share of generalists, which is contrary to many studies, which show relatedness of invertebrates to substratum type (e.g., Pilotto et al, 2015). One possible reason for divergence in conclusions may be different sampling technique.…”
Section: Bioindicationcontrasting
confidence: 77%
See 1 more Smart Citation
“…Shore alterations are linked to reduction in habitat diversity, complexity, and the loss of specific habitats such as boulders and rocks, coarse woody debris, submerged tree roots, and macrophyte stands. The metrics are similar to those used in river assessment (e.g., Böhmer et al 2004) and describe the decrease of taxon richness and diversity (Brauns et al 2007, increase of nonnative taxa (Pilotto et al 2015, Pätzig et al 2018, Porst et al 2019, increase of r-strategists (Urbanič et al 2012, and a change from more specialized and sensitive taxa toward generalists and tolerant taxa (Brauns et al 2007, Urbanič 2014. Few studies address the effects of man-made alterations to lake shorelines on macrophyte (Jusik and Macioł 2014) and fish communities (Gafny et al 1992, Mehner et al 2005, Lewin et al 2014, Cummings et al 2017.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Aroviita and Hämäläinen, 2008a;Sutela et al, 2013) or local morphological conditions (e.g. Brauns et al, 2007;Pilotto et al, 2015) which unlikely directly affect e.g. pelagial phytoplankton communities.…”
Section: Introductionmentioning
confidence: 99%